2008
DOI: 10.1007/s00424-007-0411-3
|View full text |Cite
|
Sign up to set email alerts
|

How steroid hormones act on the endothelium—insights by atomic force microscopy

Abstract: Vascular actions of steroid hormones have gained increasing importance. Indeed, some steroid hormones favorably influence vascular structure and function, whereas others are detrimental. This review will focus on the endothelial effects of steroid hormones. In the first part, we summarize data from in vivo studies elucidating the regulation of endothelial function by steroid hormones. Accumulating data argue for an improvement of endothelium-derived relaxation and impaired vascular contraction by estradiol, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 69 publications
(113 reference statements)
0
19
0
1
Order By: Relevance
“…Effects of aldosterone on a diverse range of endothelial cell functions, including NOS-dependent vasodilation (22), cell swelling and stiffness (17,25), and growth-regulatory pathways (22), have been reported. The receptor mechanisms underlying these effects have not been determined or have been presumed to be due to activation of classic or membrane-associated MRs, on the basis of the inhibitory effects of presumed mineralocorticoid-specific or selective antagonists such as eplerenone and spironolactone (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of aldosterone on a diverse range of endothelial cell functions, including NOS-dependent vasodilation (22), cell swelling and stiffness (17,25), and growth-regulatory pathways (22), have been reported. The receptor mechanisms underlying these effects have not been determined or have been presumed to be due to activation of classic or membrane-associated MRs, on the basis of the inhibitory effects of presumed mineralocorticoid-specific or selective antagonists such as eplerenone and spironolactone (20).…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone has been reported to mediate rapid endothelium-dependent vasodilation and consequent increased limb blood flow in vivo (25) and endothelium-dependent attenuation of vasoconstrictor responses in vitro (27). The effects on vascular reactivity mediated by the GPER agonist G1 parallel those mediated by aldosterone (17,20). In contrast, aldosterone-mediated vasoconstrictor effects have also been reported (1).…”
Section: Discussionmentioning
confidence: 99%
“…A change in cell elasticity to nonphysiological values disturbs these mechanisms and may result in a pathophysiological state, i.e., a disease. An increase of cell elasticity was shown for endothelial cells under high sodium conditions [48] and hyperaldosteronism [24,45], for chondrocytes in arthritis [62], for airway smooth muscle cells in bronchial asthma [2], for erythrocytes in malaria [59], for cardiac muscle in ischemia [19], and several other conditions [34]. A decrease of cell elasticity was shown for cancer cells, e.g., in bladder cancer [35] and breast cancer [21].…”
Section: Introductionmentioning
confidence: 95%
“…GPCRs are a 'hot topic' in pharmaceutical research because they are the major target of today's prescription drugs. Elasticity measurements can disclose the specific effects of pharmaceuticals [1,54,58] and hormones [24,25,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, nanoscaled approaches such as optical and magnetic traps [20][21][22][23][24], micropipette aspiration [25], shear flow [26], and atomic force microscope (AFM) [27][28][29][30][31][32][33][34][35] were demonstrated as powerful tools to investigate mechanical response in individual cells in various physiologically relevant contexts. The AFM was shown to be particularly suitable to cell mechanical studies as demonstrated in the monitoring of single cardiomyocytes beating amplitudes [30] and to the mechanical properties of various cellular models [36][37][38]. More recently, the technique was also applied to the monitoring of metabolic-driven cell membrane fluctuation in Saccharomyces cerevisiae [31,32] and to the monitoring of cell pulsation in various human cells [33,39].…”
Section: Introductionmentioning
confidence: 97%